The Translingual Literacy Movement: Optimizing Multilingual Skills through Literature: Gerakan Literasi Translingual: Mengoptimalkan Kemampuan Multibahasa Melalui Sastra - Diyan Fatimatuz Zahro (Academia Open, 2023)
This study addresses the underutilization of multilingual capabilities in Indonesia's educational system by introducing a translingual literacy movement, with literature serving as a principal tool. We utilized a systematic literature review (SLR) methodology, scrutinizing relevant publications from 2012-2022. The investigation drew from 15 sorted articles from international journals focusing on 'sastra', 'literasi', and 'translingual'. With Indonesia's rich cultural diversity, the potential for multilingual learning is significant, yet educational institutions have inadequately integrated language skills, often creating separate barriers for different languages. The translingual approach, rooted in progressivism, was explored to leverage language diversity as a resource rather than an obstacle, enabling students to better communicate and acquire useful knowledge for their self-development. Literature's role in facilitating this multilingual proficiency was emphasized, promoting imaginative and creative learning against traditional and conservative approaches. The implementation of this translingual literacy movement is expected to empower students to effectively use their multilingual abilities, fostering competitiveness in a global context. The study advocates for a reformed language learning approach, highlighting the need for proper literary resources and a conducive ecosystem to realize students' multilingual potential.Highlights: The importance of the translingual literacy movement in leveraging language diversity and optimizing multilingual abilities in Indonesia. The critical role of literature in fostering imaginative and creative learning, thus facilitating the translingual approach rooted in progressivism. The potential global competitiveness of students enhanced by effective utilization of their multilingual skills via the proposed translingual literacy movement. Keywords: Translingual Literacy, Literature, Multilingualism, Progressive Education, Language Diversity.